WORKSHOP INOVASI PELUANG USAHA ANAK MILENIAL DALAM MENAMBAH INCOME DI DESA LAU LEBAH KEC. GUNUNG SITEMBER KAB. DAIRI - Sihombing, Isra Rafika; Harahap, Dita Sayidina (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This community service activity, the main target is the young generation or millennial generation in Lau Lebah Village, District. Mount Sitembar District. Dairy. This community service activity is carried out through offline meetings. The aim of this meeting is to foster the desire for entrepreneurship, look for business opportunities and ideas for the millennial generation and society, especially in the era of digitalization and to be able to find out the challenges and obstacles in entrepreneurship and business. As for this training activity, the evaluation stage includes direct observation of participants' understanding of the material, as well as holding discussions in the form of questions and answers.